Nonsteroidal anti‐inflammatory drugs (NSAIDs) and prostate cancer risk: results from the EPICAP study. (21st September 2017) - Doat, Solene; Cénée, Sylvie; Trétarre, Brigitte; Rebillard, Xavier; Lamy, Pierre‐Jean; Bringer, Jean‐Pierre; Iborra, François; Murez, Thibaut; Sanchez, Marie; Menegaux, Florence
Abstract : Our results showed a decreased risk of prostate cancer in men using NSAIDs, especially with frequent, current, and chronic use. This effect is particularly observed in men using nonaspirin NSAIDs, and especially with preferential anti‐COX‐2 activity. Protective effect of NSAIDs seemed to be more pronounced in aggressive prostate cancer and in situation of chronic inflammation mediated by a personal history of prostatitis. Abstract: Chronic inflammation may play a role in prostate cancer carcinogenesis. In that context, our objective was to investigate the role of nonsteroidal anti‐inflammatory drugs (NSAIDs) in prostate cancer risk based on the EPICAP data. EPICAP is a population‐based case–control study carried out in 2012–2013 ( département of Hérault, France) that enrolled 819 men aged less than 75 years old newly diagnosed for prostate cancer and 879 controls frequency matched to the cases on age. Face to face interviews gathered information on several potential risk factors including NSAIDs use. Odds ratios (ORs) and their 95% confidence intervals (CIs) were calculated using unconditional logistic regression models. All‐NSAIDs use was inversely associated with prostate cancer: OR 0.77, 95% CI 0.61–0.98, especially in men using NSAIDs that preferentially inhibit COX‐2 activity (OR 0.48, 95% CI 0.28–0.79). Nonaspirin NSAIDs users had a decreased risk of prostate cancer (OR 0.72, 95% CI 0.53–0.99), particularly among men with an aggressive prostate cancer (OR 0.49, 95% CI 0.27–0.89) and in men with a personal history of prostatitis (OR 0.21, 95% CI 0.07–0.59). Our results are in favor of a decreased risk of prostate cancer in men using NSAIDs, particularly for men using preferential anti‐COX‐2 activity. The protective effect of NSAIDs seems to be more pronounced in aggressive prostate cancer and in men with a personal history of prostatitis, but this needs further investigations to be confirmed.